TO DETERMINE THE FREQUENCY OF HEPATIC VEIN VARIANTS IN NORMAL POPULATION: ROLE OF MDCT IN HEPATIC TRANSPLANTATION - Hamna Shakeel; Muhammad Ilyas; Rabia Waseem Butt; Hassan Burair Abbas; Anila Abid; Manal Niazi (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of hepatic vein variants in normal population.